Selective delivery of an anticancer drug with aptamer-functionalized liposomes to breast cancer cells in vitro and in vivo - Xing, Hang; Tang, Li; Yang, Xujuan; Hwang, Kevin; Wang, Wendan; Yin, Qian; Wong, Ngo Yin; Dobrucki, Lawrence W.; Yasui, Norio; Katzenellenbogen, John A.; Helferich, William G.; Cheng, Jianjun; et al. (Journal of materials chemistry. B, Materials for biology and medicine, 2013)
Selective targeting of cancer cells is a critical step in cancer diagnosis and therapy. To address this need, DNA aptamers have attracted significant attention as possible targeting ligands. However, while their use in targeting cancer cells has been reported, their effectiveness has rarely been established . Here we report the development of a liposomal drug delivery system for targeted anticancer chemotherapy. Liposomes were prepared containing doxorubicin as a payload, and functionalized with AS1411, a DNA aptamer with strong binding affinity for nucleolin. AS1411 aptamer-functionalized liposomes increased cellular internalization and cytotoxicity to MCF-7 breast cancer cells as compared to non-targeting liposomes. Furthermore, targeted liposomal doxorubicin improved antitumor efficacy against xenograft MCF-7 breast tumors in athymic nude mice, attributable to their enhanced tumor tissue penetration. This study suggests that AS1411 aptamer-functionalized liposomes can recognize nucleolin overexpressed on MCF-7 cell surface, and therefore enable drug delivery with high specificity and selectivity.